Study Relationship of Under Bid Price, Contract Termination, and Risk of Regional Loss - Azani, Nur; Suraji, Akhmad; Ophiyandri, Taufika (CIVED, 2024)
According to the Audit Reports of BPK Representative in West Sumatera Province with title “LHP on Compliance Audit of Regional Expenditures of West Sumatera Province for Fiscal Year of 2021”, and “LHP on Financial Statements Audit of West Sumatera Province for Fiscal Year of 2021” as well as the auction data from Electronic Procurement Portal (LPSE), it is known that there were 293 construction packages with tender procurement in West Sumatera Province during Fiscal Year of 2021. Of those 293 packages, there were 81 packages has caused public budget losses and potential budget losses with total amount of Rp1.935.987.094,02, lacks of revenue with total amount of Rp9.660.218.603,31, and there were 8 packages experienced contract termination. Of those 8 packages with contract termination, 5 packages were known to be under bid price or using bid price that was too low (less than 80% of the HPS Value). Termination of the contract has resulted in the work not being utilized for the community in a timely manner, the risk of quality degression of the abandoned work until the work is resumed, and the risk of public budget losses. This research was conducted by seeing and analyzing the bid price that is too low (under bid price) which has potential impact on contract termination and the risk of public budget losses as well as the relationship between bid price fixing issues and the causes of contract termination. This needs to be done so that the contract termination can be avoided and the results of construction works can be completed and utilized immediately. This study aims to find a causal relationship between under bid price issues and contract terminations and the risk of public budget losses through the causes that influence the occurrence of contract termination, starting from the determination of HPS and under bid price, the selection process, the preparation and the implementation of the works according to timeline. From this study, it can be concluded that under bid price has a lot of influences and is a trigger for contract termination which resulted in the risk of public budget losses. There needs to be a calculation of the real bid price by considering overhead expenses, potential increases in material and wage prices, other expenses, and unexpected expenses. In addition, the parties involved in the construction works should make a risk map in order to mitigate problems which occur during the contract implementation period. This research takes the study of water resources building construction projects. Thus, further research is still needed on the occurrence of contract termination in road and bridge construction projects.